Molecular Diagnosis of Scrub Typhus: Sample and Timing Matter - Nagarajan L Surya; Sania Paul; Susmitha K Perumalla; Karthik Gunasekaran; Abhilash KPP; Prakash JAJ (Zoonoses, 2024)
Scrub typhus (ST) is an acute febrile illness caused by Orientia tsutsugamushi . Laboratory tests are needed to confirm the diagnosis when the characteristic eschar is absent. This study aimed to evaluate the performance of 47 kDa qPCR using clotted and EDTA-treated blood among patients with suspected ST Clotted blood samples from 284 inpatients (IPs) and EDTA-treated blood samples from 194 outpatients (OPs) with suspected scrub typhus were collected from patients who were blood culture- and malaria-negative. ST IgM ELISA and 47 kDa qPCR were performed for detection of ST infections. Among the IPs (n=284) and OPs (n=194), 41% and 63% were confirmed to have ST based on the case definition, respectively; the mortality rate was 1%. The 47 kDa qPCR sensitivity of the buffy coat (65.6%) was greater compared to clotted blood (37.1%). PCR was more likely to be positive in the 1st week of the illness; IgM ELISA positivity increased after the 5th day of the illness. The type of sample and the time of sample collection have a role in the diagnosis of ST. These preliminary results need to be confirmed by prospective multicentric studies.